The 2024 Asian–Australian Monsoon Year: Widespread Extremes with Notable Subseasonal Variability and Socioeconomic Impacts - Lin Wang; Zizhen Dong; Tim Cowan; Peng Hu; Shiromani Jayawardena; Maheswar Pradhan; Hui Su; Thea Turkington; Wei Gu; Seok-Woo Son; Donaldi Sukma Permana; Rajashree Naha; et al. (Journal of Meteorological Research, 2026)

Source and fate of atmospheric iron supplied to the subarctic North Pacific traced by stable iron isotope ratios - Minako Kurisu; Kohei Sakata; Jun Nishioka; Hajime Obata; Tim M. Conway; Hannah R. Hunt; Matthias Sieber; Katsuhiko Suzuki; Teruhiko Kashiwabara; Sayuri Kubo; Makoto Takada; Yoshio Takahashi (Geochimica et Cosmochimica Acta, 2024)

Source apportionment of mine contamination across streamflows - Patrizia Onnis; Patrick Byrne; Karen A. Hudson-Edwards; Ilaria Frau; Tim Stott; Tom Williams; Paul Edwards; Chris O. Hunt (Applied Geochemistry, 2023)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Hierarchical analysis of wild Atlantic salmon ( Salmo salar ) fecundity in relation to body size and developmental traits - Nora Hanson; James Ounsley; Tim Burton; Sonya Auer; James H. Hunt; Brian Shaw; Jim Henderson; Stuart J. Middlemas (Journal of Fish Biology, 2020)
Using data from wild Atlantic salmon Salmo salar returning to spawn in seven Scottish rivers, we developed a model of fecundity based on individual body size and key developmental traits. We used a novel approach to model selection which maximises predictive accuracy for application to target river stocks to select the best from a suite of Bayesian hierarchical models. This approach aims to ensure the optimal model within the candidate set includes covariates that best predict out‐of‐sample data to estimate fecundity in areas where no direct observations are available. In addition to body size, the final model included the developmental characteristics of age at smolting and years spent at sea. Using two independent long‐term monitoring datasets, the consequences of ignoring these characteristics was revealed by comparing predictions from the best model with models that omitted them.

Photographic Capture-Recapture Analysis Reveals a Large Population of Indo-Pacific Bottlenose Dolphins (Tursiops aduncus) With Low Site Fidelity off the North West Cape, Western Australia - Rebecca Haughey; Tim Hunt; Daniella Hanf; Robert William Rankin; Guido J. Parra (Frontiers in Marine Science, 2020)

Regional-scale Proterozoic IOCG-mineralized breccia systems: examples from the Wernecke Mountains, Yukon, Canada - Julie Hunt; Tim Baker; Derek Thorkelson (Mineralium Deposita, 2005)

Mapping of a discontinuous and highly conformational binding site on follicle stimulating hormone subunit-β (FSH-β) using domain Scan™ and Matrix Scan™ technology - Peter Timmerman; Evert Van Dijk; Wouter Puijk; Wim Schaaper; Jerry Slootstra; Stephen J. Carlisle; John Coley; Steve Eida; M. Gani; Tim Hunt; Paul Perry; Gerry Piron; et al. (Molecular Diversity, 2004)